Blackout Recovery Scenario in a Combined-Cycle Power Plant via Line Charging and Internal Cross-Supply: A Techno-Economic Comparative Analysis - Warih, Gamal Fiqih Handono; Jufri, Fauzan Hanif; Samual, Muhammad Gillfran; Hudaya, Chairul (International Journal of Electrical, Computer, and Biomedical Engineering, 2024)
The readiness of fast response power plants, such as Combined-Cycle Power Plant (CCCP), following a blackout in the power system shall be maintained to preserve the availability of the supply. Hence, blackout recovery scenario is usually prepared and considered as one of the measures to achieve the system readiness after blackout. This study presents a techno-economic comparative analysis between two blackout recovery methods, namely via line charging and internal cross-supply, in CCCP Priok, Indonesia. It analyzes the historical data of the relationship of the active power contribution to the frequency, and then obtains the appropriate settings for the power plant parameters. From the technical perspective, the gain value or participation factor of this plant is 49 MW/Hz with 6% droop setting and 0.029 Hz of deadband frequency. It is found that a load set point lower than 2.49 MW can lead to grid synchronization failure since there are self-consumption loads on each gas turbine. Moreover, to prevent the risk of reverse power and to achieve a successful internal cross-supply scenario, the minimum load setting shall be adjusted to 3 MW. Meanwhile, from an economic perspective, the results show that a successful internal cross-supply method may save up to IDR 2.7 billion compared with line charging method.